The impact of changing the urban planning of historical centers on the spatial environment of the city (a Najaf city is a model) - Al-Tamimi, Ahmed Hani; Al-Mamoori, Sohaib Kareem; Al-Maliki, Laheab A. (AIP conference proceedings, 2023)
Many researchers are interested in studying the pressures in historical areas due to the continued development to meet the requirements of contemporary society. The study scope was set by looking at the factors that lead to the addition or removal of the urban fabric to make a city more urban. This may lead to these forced changes overlooking the historical context of these cities in favour of demolishing and removing large parts of the city’s fabric and replacing them with buildings with modern and random building patterns. The study tried to see if the " ill-thought-out change in land use planning affects identifying different parts of the city’s urban fabric body, mainly traditional parts. " Within a realistic urban fabric represented by the old city of Najaf Ashraf in Iraq as one of the important urban and heritage landmarks globally and containing different models and patterns and subjecting them to different political, economic, and economic circumstances social. The research emphasized dealing with the urban environment as an integrated content consisting of a set of visible and latent systems of parts, including the urban fabric, whose elements are linked to each other in complex relationships carrying civilized and urban values, subject to natural and coercive changes in the level of their urban fabric. The research concluded that change at some point could lead to heterogeneity with neighboring countries if specific building laws and regulations were not enacted governing the process of change and regulating the process of linking the old and the modern.